Strategy for Settlement Area with Eco-Waterfront Approach in Lakkang Island, Makassar City - Ayu, Ana Dian; Arifin, Mimi; Wunas, Shirly (Journal of Asian Multicultural Research for Social Sciences Study, 2022)
This study aims to analyze the site structure of houses and their supporting facilities for zones that face the waters of Lakkang Island, to analyze the attractiveness and tourist visits that can influence the development of supporting functions for residents’ activities in the waterfront area of Lakkang Island, and to develop a structuring strategy. This research employs observation, interviews, documentation surveys, and theoretical studies as data gathering methods. Spatial, comparative, and SWOT analysis are used as study methods. According to the findings of the study, the site structure of houses in water-oriented zones consists of water zones, such as rivers, ponds, and mangrove vegetation, which are the center of community activities such as fishing and farming, river border zones, such as rice fields, and settlements in the region. Located on the riverside, where the rice fields on Lakkang Island can only be harvested once a year, and where the villages along the river boundary consist of 35 homes fewer than 100 meters apart. The settlement zone and its supports, i.e. the pattern and orientation of buildings, tend to be linear, following the road and river, with street-facing orientation predominating. The type is characterized by non-stilt structures, whereas permanent structures dominate the construction materials. Bamboo groves are often utilized as photo locations, and there is a bunker on home property.